The physical and mechanical properties of polyurethanes from oleic acid polyols - Velayutham, T.S.; Abd Majid, Wan Haliza; Ahmad, A.B.; Gam, Y.K.; Gan, S.N. (Wiley, 2009)
Three different polyester polyols, with various oleic acid content, were used in the preparation of polyurethane (PUR) coatings. The polyols were designated as Alk28, Alk40, and Alk65, in which 28, 40, and 65 represent the percentage of oleic acid of the polyol formulations. These polyester polyols were reacted with aromatic diisocyanate toluene diisocyanate (TDI) to form PUR coatings. The acid value, hydroxyl value, molecular weight, and viscosity of the polyols have been determined. The reaction between the polyols and TDI was studied by Fourier Transform Infrared spectroscopy and X-ray diffraction (XRD). The effects of varying NCO/OH ratio and oleic acid content of polyols on physical and mechanical properties of PUR films were studied. XRD results indicate that the samples are amorphous. PURs, made with Alk28, have the best mechanical properties followed by Alk40 and Alk65. The mechanical properties of the samples have increased as the NCO/OH ratio was increased from 1.2 to 1.6. Â© 2009 Wiley Periodicals, Inc.